THE EFFECT OF PROFITABILITY AND COMPANY SIZE ON COMPANY VALUE WITH DIVIDEND POLICY AS AN INTERVENING VARIABLE - Uyun, Lailatul; Mastiah, Mastiah (Yayasan Education and Social Center, 2025)
The purpose of this research is to know the direct effect of profitability, company size on company value on company value and knowing dividend policy can mediate the relationship between profitability and dividend policy with company value on the LQ 45 index in 2018-2024 listed on the Indonesia Stock Exchange. The research method used is quantitative with a correlational approach.The population in this study is LQ 45 companies in 2018-2024 listed on the Indonesia Stock Exchange. The research sample was 15 companies in the LQ 45 Index for the 2018-2024 period. The results of the analysis show that 1)return on asset has a significant positive effect on price to book value, 2) company size has a significant positive effect on price to book value, 3) return on asset has no significant positive effect on dividend payout ratio, 4) company size has a significant negative effect on dividend payout ratio, 5) dividend payout ratio has no effect on price to book value, 6) return on asset and company size to price to book value through dividend payout ratio, the results obtained are that the result of the multiplication of direct influence is greater than the value of the indirect influence.